Pākehā and Tauiwi Treaty education: an unrecognised decolonisation movement?. (2nd July 2016) - Huygens, I
ABSTRACT: The Māori call to honour Te Tiriti o Waitangi is arguably the oldest continuous social movement in Aotearoa New Zealand since the Treaty for European settlement was signed. A much more recent Pākehā and Tauiwi activism for the Treaty has supported the Māori movement, but is often overlooked as a social movement. Responsibility for ensuring that Tauiwi understand the Treaty remains contentious—is Treaty education a Tauiwi or a Māori responsibility? This article describes the emergence in the 1980s of a consensus among Māori and Tauiwi activists that, as Treaty partners, Pākehā/Tauiwi should take responsibility for their own learning about Te Tiriti and colonisation. Six reasons for overlooking such decolonising education as a social movement are explored through reflexive scholarship by Treaty educators: 1. hegemonic views of social change movements as only class- or race-based and adversarial; 2. Tiriti education as counter-hegemonic education that encourages transformation of the Māori–Pākehā relationship; 3. confusion over whether the aims of Treaty education are counter-hegemonic or assimilatory; 4. the movement's evolving membership to include many cultural identities and activism about diverse neo-colonialisms; 5. its focus on mutually-agreed relationship-building; and 6. the complexity of assessing its impact and contribution to a decolonisation agenda.